Hydroxyapatite as a Nanomaterial for Advanced Tissue Engineering and Drug Therapy - Tuukkanen, Juha; Nakamura, Miho (Current Pharmaceutical Design, 2017)
Hydroxyapatite (HAp) is a complicated ceramic material that varies between the way it appears in biological systems and how it is synthesized as various calcium phosphates. HAp varies in chemical composition of substituting atoms, crystallinity, grain size and electrical polarization. HAp can form solid to macro-, micro- and nanoporous structures. Also, particulate HAp can have highly porous structure. HAp can be used as coatings for metal implants in thicknesses from hundreds of microns down to hundreds of nanometers. Cotton wool-like HAp fibers can be electrospun compounded with polymers (or without) for tissue engineering (TE) scaffolds. This review describes the features of HAp that may be utilized further in developing novel applications. As a nanomaterial HAp has been applied for drug delivery. The adsorption of proteins and other compounds can be adjusted by modifying HAp composition, electrical polarization and wettability. Of special interest are the bisphosphonates that bind to HAp and thereby can be used to treat bone loss and also couple other drugs to the mineral. A new area for HAp constructs may appear in treating metallosis. HAp coating may function as a scavenger for the ions release from metal implants and thereby inhibit the adverse effects of the ion burden for the body. So far HAp is considered as safe biomaterial but nano HAp may insidiously possess adverse effects especially when ingested by cells and eliciting excess intracellular calcium. Thereby critical approach also for HAp biomaterials is of utmost importance.
Keywords: mineral